2002
DOI: 10.1021/ma0120963
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Free Volume in Glassy Poly(ethylene terephthalate)

Abstract: Positron annihilation lifetime measurements have been carried out for glassy poly(ethylene terephthalate) (PET) as a function of temperature in the temperature range from 15 to 300 K. The structural relaxation and transition were studied by positron annihilation lifetime spectroscopy (PALS). According to the variation of orthopositronium(o-Ps) lifetime with temperature, two intercept temperatures were observed and were designated as the secondary transition temperatures T γ (γ transition) and Tβ (β transition)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…For most of the polymers, Ps formation in (the densely packed) crystals could not be observed; [71] an extra lifetime of about 1 ns attributed to polymer crystals has only been confirmed for polyethylene and poly(tetrafluoroethylene). [68] The analysis of our spectra from below the melting point using the routines CONTIN, MELT, and LT9.0 did not show any indication of an extra, medium o-Ps lifetime.…”
Section: Positron Lifetime Spectra and Their Analysesmentioning
confidence: 99%
“…For most of the polymers, Ps formation in (the densely packed) crystals could not be observed; [71] an extra lifetime of about 1 ns attributed to polymer crystals has only been confirmed for polyethylene and poly(tetrafluoroethylene). [68] The analysis of our spectra from below the melting point using the routines CONTIN, MELT, and LT9.0 did not show any indication of an extra, medium o-Ps lifetime.…”
Section: Positron Lifetime Spectra and Their Analysesmentioning
confidence: 99%
“…Positron annihilation lifetime spectroscopy has been used as a unique technology to probe the free volume properties of polymers for many years 11, 12. PALS was proven to be sensitive to atom‐scale free volume holes of polymers, due to the formation of the positronium (Ps) atom, which is a bound state of e + and e − .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the fractional free volume f is evaluated in terms of the o ‐Ps intensity I 3 and the size of free volume hole ( $V={4\over 3}{\rm \pi}R^3$ ): where C is a constant. Usually, we use apparent free volume fraction, f app : because what we concerned is not the absolute value of free volume fraction, but instead the variation of free volume fraction 12…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Utraki et al reported the free-volume fraction of an exfoliated poly(e-caprolactam) (PA-6)/montmorillonite (MMT) nanocomposite estimated by pressure-volumetemperature (PVT) measurement. Compared with the matrix, incorporation of 1.6 wt.-% MMT reduced the freevolume fraction by 14%.…”
Section: Introductionmentioning
confidence: 99%